Los rincones de trabajo como actividad lúdica y su relación con el aprendizaje de los niños y niñas de nivel 2 de la escuela fiscal “José Antonio Campos“, del cantón Zapotillo, provincia de Loja, en el período 2014 – 2015.” Lineamientos propositivos - Sánchez Rogel, Wilma Elizabeth (2014)
This research was part of the analytical, descriptive and explanatory study: CORNERS OF WORK AS LEISURE ACTIVITY AND ITS RELATIONSHIP WITH LEARNING CHILDREN OF THE FISCAL LEVEL 2 SCHOOL "JOSÉ ANTONIO CAMPOS" Zapotillo CANTON, PROVINCE Loja, 2014-2015. GUIDELINES propositional was structured and developed in accordance with the Rules of the Academic Board of the National University of Loja. Raised the overall objective: To determine the relationship Corners Working as Playful Learning Activity and children of level 2 school tax "José Antonio Campos" Zapotillo Canton province of Loja, in the period 2013 - 2014 The methods used in the development of this investigation were: scientific, analytic, synthetic, deductive, inductive, descriptive, and statistical model, they allow us to relate the work corners as recreational activity in the teaching-learning process. The techniques applied were: the survey of teachers ranging from pre to identify the corners of Labour and an observation guide for assessing learning. From the results of the survey of teachers concluded that: EL 100% of the teachers surveyed say they have within their classroom Corner construction and 50% say they have the corner of Plastic. According to the results of the implementation of the Observation Guide is concluded that: EL 100% of the teachers surveyed say they have within their classroom Corner construction and 50% say they have the corner of Plastic; and 40% of boys and girls show a Learning investigated whose indicator is Started, 31% in the indicator process and 29% in the Acquired indicator.